Harvesting system suitability as decision support in selection cutting forest management in Northwest Bosnia and Herzegovina - Marčeta, Dane (Array, 2020)
Planning of forest harvesting operations is one of the key elements of successful forest management. The integration of modern tools and traditional forestry procedures is something that must be done in contemporary forestry. This research investigated the use of multicriteria decision support (AHP) and GIS in choosing the optimal harvesting system for predominantly selection cutting forest management on the example of two Forest Management Units (FMU). Results showed that AHP could be easily integrated into GIS using the extAHP tool and its results could be of help, along with other input data, in choosing the optimal harvesting system. Spatial analysis of raster data in GIS gives a comprehensive insight into the stand and terrain characteristics and shows the relative share of the area proposed for each system. In FMU »Kozara–Mlječanica«, the harvesting system chainsaw-skidder had the highest relative share with 44% of the area, meaning that it is almost the only harvesting system in current use, followed by chainsaw-forwarder (36%), chainsaw-cable yarder (19%), and chainsaw-adapted agriculture tractor (AAT) (1%). The system harvester-forwarder was not used at all, which is understandable considering that FMU »Kozara–Mlječanica« has a higher average slope and higher diameter of trees to be cut than FMU »Prosara«, where harvester-forwarder system accounts for a significant 36% of the area. The dominant system in FMU »Prosara« was chainsaw-forwarder (42%), followed by chainsaw-cable yarder (17%), chainsaw-skidder (4%) and chainsaw-AAT (1%). It should be noted that the presence of chainsaw-skidder system is insignificant. It is replaced by the system chainsaw-forwarder. Traditional harvesting system chainsaw-skidder, which prevails in Bosnia and Herzegovina, should be upgraded with the new technologies and methods. Using tools like multicriteria decision support and GIS could be of great help in that process.